Revisión sobre la enseñanza de la física en estudiantes con diversidad funcional visual - Castro-Castillo, Diana-Carolina; Tuay-Sigua, Rosa-Nidia (Revista Científica, 2023)
In the teaching of science, experiences are carried out which seek for students to develop skills to describe and compare phenomena or make measurements, prioritizing the sense of vision. This leads to reflect on particular strategies when this sense is lacking. For this reason, in recent years, a set of actions derived from the public education policy have been undertaken, which have made it possible to include people with visual functional diversity (VFD) in the teaching and learning processes of physics, thus allowing for continuous reflection on pedagogical and didactic aspects in which the sensory conditions of the students are recognized. To identify the theoretical and methodological advances in this field, a review of articles was carried out, with an observation window from 2010 to 2022, using different databases and searching in journals specialized in the teaching of physics. It was found that it is an emerging field of research in which progress has been made with respect to adaptation, the construction of didactic material, and software design, so that this community can access the explanations given within the framework of science on phenomena of the natural world, making use primarily of the senses of touch and hearing.